Electrocatalytic oxidation of benzyl alcohol for simultaneously promoting H2 evolution by a Co0.83Ni0.17/activated carbon electrocatalyst. (29th March 2018) - Liu, Guoqiang; Zhang, Xian; Zhao, Cuijiao; Xiong, Qizhong; Gong, Wanbing; Wang, Guozhong; Zhang, Yunxia; Zhang, Haimin; Zhao, Huijun
Abstract : Co0.83 Ni0.17 alloy nanoparticles on activated carbon were successfully fabricated by a simple thermal-treatment method, as electrocatalyst exhibiting superior HER, OER and electrocatalytic oxidation activity toward benzyl alcohol. Abstract : Electrocatalytic water splitting as an environmentally friendly method to produce clean H2 has attracted wide attention. However, efficient improvement of the performance of the oxidation half-reaction during water splitting, thus enhancing H2 evolution efficiency, has become an urgent issue. Herein, non-precious metal Co0.83 Ni0.17 alloy nanoparticles on activated carbon (Co0.83 Ni0.17 /AC) have been successfully fabricated by a simple thermal-treatment method. The resulting Co0.83 Ni0.17 /AC with a dominant alloy particle size of 45 nm exhibits a microporous and mesoporous structure with a surface area of 159.2 m 2 g −1 . As an electrocatalyst, the as-prepared Co0.83 Ni0.17 /AC demonstrates bifunctional electrocatalytic activity toward the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in alkaline media, delivering overpotentials of 193 and 325 mV at 10 mA cm −2, respectively. Importantly, it is found that the electrocatalytic oxidation of benzyl alcohol to benzoic acid on Co0.83 Ni0.17 /AC is more favourable than the OER process, with almost 224 mV less overpotential at 10 mA cm −2 and 96% faradaic efficiency at 1.425 V vs. RHE (passing charge amount of ∼40C). As a simultaneous anode and cathode electrocatalyst for water splitting, Co0.83 Ni0.17 /AC displays a H2 generation rate of 8.98 μmol min −1 in 1.0 M KOH solution containing 10 mM benzyl alcohol, almost 1.4 times that obtained by an OER-introduced water splitting system, with near 98% faradaic efficiency for H2 . This work would be helpful to develop low-cost and abundant bifunctional electrocatalysts for electrocatalytic organic synthesis and simultaneously improving H2 generation from water splitting.